[OP.8B.08] HIGH SODIUM INTAKE IN TREATED BUT UNCONTROLLED HYPERTENSIVE PATIENT. (September 2017) - Rhee, M.; Kim, J.; Shin, S.; Nah, D.; Gu, N.; Sung, K.; Hong, K.; Park, D.
Abstract : Objective: Although high sodium intake in hypertensive patients has been shown, in most studies, blood pressure (BP) was measured by conventional method, not by ambulatory BP monitoring. Advantage of ambulatory BP monitoring is diagnosis of masked or white-coat hypertension. It is unclear whether the association between high sodium intake and the level of BP may persist when BP is measured by ambulatory BP monitoring. Design and method: Among the 1121 participants (998 invited by random digit-dial from five cities, 123 volunteers), 740 participants who had complete 24-h urine collection and valid 24-h ambulatory BP monitoring were analyzed. Participants were grouped in 4 groups; normotensives (NT, n = 438), untreated hypertensives (HT) (n = 173), treated and controlled HT (n = 66), and treated but uncontrolled HT (n = 63). Results: Treated HT showed higher mean age than untreated HT. Treated but uncontrolled HT had highest body mass index (BMI) and 24-h urine sodium, similar 24-h systolic and diastolic BP to untreated HT, but higher 24-h systolic and diastolic BP than NT and treated and controlled HT. Multivariate analysis adjusted with age, gender, and BMI showed highest level of 24-h urine sodium in treated but uncontrolled HT among the four groups. Conclusions: Highest level of 24-h urine sodium in treated but uncontrolled HT suggests that high sodium intake may have an adverse effect on BP lowering in hypertensive patients taking antihypertensive drugs.